MAGNETOCALORIC EFFECT AND ELECTRONIC PROPERTIES OF DOPED INSB - DOUBLE QUANTUM WIRE IN THE PRESENCE OF EM-FIELDS AND SPIN- ORBIT TERM - Ali, Mahmoud M. (An-Najah National University, 2025)
This study provides a comprehensive theoretical analysis of the electronic, magnetic, and thermodynamic properties of a double quantum wire (DQW) system made of Indium Antimonide (InSb), a material known for its high electron mobility and strong spin-orbit coupling. The study investigates the effect of the structural parameters of the confining potential, Rashba spin-orbit, external electric and magnetic fields, and impurity potential on the electronic, magnetic, and thermodynamic properties. We solve the Hamiltonian by using the exact diagonalization method, and then we compute the energy spectra, probability density distributions, local density of states (LDOS), magnetization, magnetic susceptibility, entropy, and magnetocaloric effect (MCE) for the double quantum wire system. Our numerical results show that the presence of the dopant potential changes the electronic structure, causing energy level shifts and breaking the symmetry between the two quantum wires. The impurity causes selective energy shifts, so that one wire undergoes large spectral changes while the other wire remains largely unchanged. Furthermore, the energy spectra and the probability density distributions analysis indicates that the quantized energy levels strongly depend on the structural parameters of the confining potential. The observed energy splitting and redistribution of probability density shows that the external fields provide a mechanism for controlling electronic properties for the system. Additionally, The effect of Rashba SOC and magnetic field variations on LDOS and spin-split state formation is explained. The influence of temperature, SOC strength, and electric field on the magnetic properties is analyzed, focusing on the transition from diamagnetic to paramagnetic behavior. The interplay between quantum and thermal effects is discussed. Our results highlight the critical role of spin-orbit coupling and external fields in controlling the magnetic responses. The MCE is studied by calculating entropy change and the refrigerant capacity (RC). We found that the refrigerant capacity (RC) increases nonlinearly with the Rashba spin-orbit coupling (SOC) strength. It is further enhanced when the impurity is placed at a specific position and when the external electric field is increased up to a certain value. These findings offer valuable insights for optimizing magnetocaloric materials for advanced technologies.
التاثير المغناطيسي الحراري والخصائص الالكترونية لسلك كمي مزدوج مع وجود شوائب ومجالات كهربائية و مغناطيسية خارجية